On psychopathology - "Freud, Sigmund" (Middlesex Eng, 1983)
On Psychopathology contains major writings on mental illness, its varieties and the ways in which it develops. It is arranged by subject matter, and brings together papers published as early as 1895 and as late as 1926. In this way the reader can trace the historical evolution of Freud's ideas. The earliest paper is his classical account of ánxiety neurosis', a term coined by Freud which was to win such general acceptance that its origin is now usually overlooked.
Keywords: Psychology